Overcoming treatment resistance in cholangiocarcinoma: current strategies, challenges, and prospects - Wang, Jiayi; Liu, Siyan; Cao, Yi; Chen, Yong (Frontiers in Cell and Developmental Biology, 2024)
Significant advancements in our understanding and clinical treatment of cholangiocarcinoma (CCA) have been achieved over the past five years. Groundbreaking studies have illuminated the immune landscape and pathological characteristics of the tumor microenvironment in CCA. The development of immune-and metabolism-based classification systems has enabled a nuanced exploration of the tumor microenvironment and the origins of CCA, facilitating a detailed understanding of tumor progression modulation. Despite these insights, targeted therapies have not yet yielded satisfactory clinical results, highlighting the urgent need for innovative therapeutic strategies. This review delineates the complexity and heterogeneity of CCA, examines the current landscape of therapeutic strategies and clinical trials, and delves into the resistance mechanisms underlying targeted therapies. Finally, from a single-cell and spatial transcriptomic perspective, we address the challenge of therapy resistance, discussing emerging mechanisms and potential strategies to overcome this barrier and enhance treatment efficacy.